Germline landscape of BRCAs by 7-site collaborations as a BRCA consortium in Turkey. (October 2022) - Bisgin, Atil; Sag, Sebnem Ozemri; Dogan, Muhammet E.; Yildirim, Mahmut S.; Gumus, Aydeniz Aydin; Akkus, Nejmiye; Balasar, Ozgur; Durmaz, Ceren D.; Eroz, Recep; Altiner, Sule; Alemdar, Adem; Aliyeva, Lamia; et al.
Abstract: BRCA1/2 mutations play a significant role in cancer pathogenesis and predisposition particularly in breast, ovarian and prostate cancers. Thus, germline analysis of BRCA1 and BRCA2 is essential for clinical management strategies aiming at the identification of recurrent and novel mutations that could be used as a first screening approach. We analyzed germline variants of BRCA1/2 genes for 2168 individuals who had cancer diagnosis or high risk assessment due to BRCAs related cancers, referred to 10 health care centers distributed across 7 regions covering the Turkish landscape. Overall, 68 and 157 distinct mutations were identified in BRCA1 and BRCA2, respectively. Twenty-two novel variants were reported from both genes while BRCA2 showed higher mutational heterogeneity. We herein report the collective data as BRCA Turkish consortium that confirm the molecular heterogeneity in BRCAs among Turkish population, and also as the first study presenting the both geographical, demographical and gene based landscape of all recurrent and novel mutations which some might be a founder effect in comparison to global databases. This wider perspective leads to the most accurate variant interpretations which pave the way for the more precise and efficient management affecting the clinical and molecular aspects. Highlights: A similar percentage of clinically unaffected individuals were also identified with potentially pathogenic variants. Based on the geographic examinations, Eastern Anatolian and the Mediterranean region had the lowest positivity rates. The Southeastern Anatolian region showed the lowest density of both patients and clinically relevant genetic changes.